2015
DOI: 10.1002/dta.1786
|View full text |Cite
|
Sign up to set email alerts
|

Redox proteomic analysis of mytilus edulis gills: effects of the pharmaceutical diclofenac on a non‐target organism

Abstract: Veterinary and human pharmaceuticals are an emerging category of chemical pollutants with potential to cause serious toxicity to non-target organisms. Filter-feeding aquatic organisms such as mussels are especially threatened. In this study, the blue mussel, Mytilus edulis, was exposed to two doses (0.2 mg/L and 1 mg/L) of the anti-inflammatory diclofenac. Effects on the gill, the principal feeding organ of mussels, were investigated. It was noted that, while no effect was evident on gill glutathione transfera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
(94 reference statements)
2
6
0
Order By: Relevance
“…The level of GST response was higher compared to GR. This agrees with the previous reported studies (Song et al, 2012;Jaafar et al, 2015;Gianng et al, 2018).…”
Section: Glutathione-dependent Enzymes Systemsupporting
confidence: 94%
See 2 more Smart Citations
“…The level of GST response was higher compared to GR. This agrees with the previous reported studies (Song et al, 2012;Jaafar et al, 2015;Gianng et al, 2018).…”
Section: Glutathione-dependent Enzymes Systemsupporting
confidence: 94%
“…All samples were extracted using homogenizer (ULTRA TURREX) in 10 mM Tris -HCL buffer (pH 7.2) and the post-mitochondrial supernatants (PMS) was obtained after centrifugation at 15000 X g and 4ºC for one hour (Jaafar et al, 2015). Protein mass determination was done for all samples following Bradford assay using Bovine Serum Albumin (BSA) as a standard (Bradford, 1976).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The IDP3 gene encodes peroxisomal NADP-dependent isocitrate dehydrogenase (ICDH), which catalyzes the oxidation of isocitrate to form alpha-ketoglutarate and NAD(P)H (Lu and McAlister-Henn, 2010). Environmental stresses, such as nutrient stress, temperature alteration, and tobacco smoking, have been shown to modulate ICDH activity (Konga et al, 2009; Jaafar et al, 2015). NAD(P)H is an effective scavenger of free radicals and hydrogen peroxide; thus ICDH might also act as an indirect antioxidant by providing NAD(P)H, which is required in corneal defense against oxidative damage (Lassen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…individual, but studies have found that Mytilus californianus is capable of filtering at a rate of 50 -3000 mL/min (Bayne et al, 1976). This unique and important organ, serving a dual purpose for bivalve feeding and respiration, makes it a common focal tissue for studies of Mytilus stress physiology (Dahlhoff et al, 2002;Jaafar et al, 2015;Letendre et al, 2009;McDonagh et al, 2006;Rocher et al, 2015;Tomanek and Zuzow, 2010). Furthermore, the direct interaction between the gill tissue of sessile bivalves and their environment leaves them acutely exposed to pollutants, making this organ of great interest for research supporting ecotoxicological monitoring programs (Gómez-Mendikute et al, 2005).…”
Section: Mytilus Gill Physiologymentioning
confidence: 99%